Considerable Variation of Antibacterial Activity of Cu Nanoparticles Suspensions Depending on the Storage Time, Dispersive Medium, and Particle Sizes. (3rd August 2015) - Zakharova, Olga V.; Godymchuk, Anna Yu.; Gusev, Alexander A.; Gulchenko, Svyatoslav I.; Vasyukova, Inna A.; Kuznetsov, Denis V.
Abstract : Suspensions of Cu nanoparticles are promising for creating the new class of alternative antimicrobial products. In this study we examined copper nanoparticles of various sizes obtained by the method of wire electric explosion: nanopowder average size 50 nm (Cu 50) and 100 nm (Cu 100). The paper presents the complex study of the influence of physicochemical properties such as particle size and concentration of the freshly prepared and 24-hour suspensions of Cu nanoparticles in distilled water and physiological solution upon their toxicity to bacteria E. coli M-17. Ionic solution of Cu 2+ and sodium dichloroisocyanurate was used for comparison study. It has been shown that decrease in the nanoparticle size leads to changes in the correlation between toxicity and concentration as toxicity peaks are observed at low concentrations (0.0001⋯0.01 mg/L). It has been observed that antibacterial properties of Cu 50 nanoparticle suspensions are ceased after 24-hour storage, while for Cu 100 suspensions no correlation between antibacterial properties and storage time has been noted. Cu 100 nanoparticle suspensions at 10 mg/L concentration display higher toxicity at substituting physiological solution for water than Cu 50 suspensions. Dependence of the toxicity on the mean particle aggregates size in suspension was not revealed.